DEHYDRATION MELTING OF METABASALT AT 8-32 KBAR: IMPLICATIONS FOR CONTINENTAL GROWTH AND CRUST-MANTLE RECYCLING - Rapp R.P.; Watson E.B. (My University, 1995)
We report the results of partial melting experiments between 8 and 32 kbar, on four natural amphibolites representative of metamorphosed Archean tholeiite (greenstone), high-alumina basalt, low-potassium tholeiite and alkali-rich basalt. For each rock, we monitor changes in the relative proportions and composition of partial melt and coexisting residual (crystalline) phases from 1000 to 1150°C, within and beyond the amphibole dehydration reaction interval. Low percentage melts coexisting with an amphibolite or garnet amphibolite residue at 1000–1025°C and 8–16 kbar are highly silicic (high-K2O granitic at ?5%; melting, low-Al2O3 trondhjemitic at ?5–10%). Greater than 20% melting is only achieved beyond the amphibole-out phase boundary. Silicic to intermediate composition liquids (high-Al2O3 trondhjemitic-tonalitic, granodioritic, quartz dioritic, dioritic) result from ?20–40% melting between 1050 and 1100°C, leaving a granulite (plagioclase + clinopyroxene ? orthopyroxene ? olivine) residue at 8 kbar and garnet granulite to eclogite (garnet + clinopyroxene) residues at 12–32 kbar. Still higher degrees of melting ( ?40–60%) result in mafic liquids corresponding to low-MgO, high-Al2O3 basaltic and basaltic andesite compositions, which coexist with granulitic residues at 8 kbar and edogitic or garnet granulitic (garnet + clinopyroxene + plagioclase ? orthopyroxene) residues at higher pressures (12–28 kbar). As much as 40% by volume high-Al2O3 trondhjemitic-tonalitic liquid coexists with an eclogitic residue at 1100–1150°C and 32 kbar. The experimental data suggest that the Archean tonalite-trondhjemite-granodiorite (TTG) suite of rocks, and their Phanerozoic equivalents, the tonalite-trondhjemite-dacite suite (including ‘adakites’ and other Na-rich granitoids), can be generated by 10–40% melting of partially hydrated metabasalt at pressures above the garnet-in phase boundary (?12 kbar) and temperatures between 1000 and 1100°C. Anomalously hot and/or thick metabasaltic crust is implied. Although a rare occurrence along modern convergent plate margins, subductionrelated melting of young, hot oceanic crust (e.g. ocean ridges) may have been an important (essential) element in the growth of the continental crust in the Archean, if plate tectonic processes were operative. Coupled silicic melt generation-segregation and mafic restite disposal may also occur at the base of continental or primitive (sub-arc?) crust, where crustal overthickening is a consequence of underplating and overaccretion of mafic magmas. In either setting, net growth of continental crust and crustmantle recycling may be facilitated by relatively high degrees of melting and extreme density contrasts between trondhjemitictonalitic liquids and garnet-rich residues. Continuous chemical trends are apparent between the experimental crystalline residues, and mafic migmatites and garnet granulite xenoliths from the lower crust, although lower-crustal xenoliths in general record lower temperatures (600–900°C) and pressures (5–13 kbar) than corresponding residual assemblages from the experiments. However, geo-thermobarometry on eclogite xenoliths in kimberlites from the subcontinental mantle indicates conditions appropriate for melting through and beyond the amphibole reaction interval and the granulite-eclogite transition. If these samples represent ancient (eclogitized) remnants of subducted or otherwise foundered basaltic crust, then the intervening history of their protoliths may in some cases include partial melting.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей